Trends and Mapping of STEAM-based Interactive Media: A Systematic and Bibliometric Review - Munif, Dewi Himatul; Subali, Bambang (Universitas Negeri Semarang, 2025)
Integrating interactive digital media with the STEAM approach is considered a potential solution to increase student engagement, creativity, and critical thinking. This study aims to systematically review the development and implementation of STEAM-based interactive learning media for education during 2016-2025. The method used was a systematic literature review by analyzing national and international publications relevant to STEAM integration, interactive media design, and learning outcomes in science education. In addition, this study also used a bibliographic analysis method. From 409 initial articles, 66 articles were selected for full review, and 16 articles met the inclusion criteria. Content analysis was conducted to examine the types of media, pedagogical approaches, education levels, and reported learning outcomes. All studies reported that interactive media have high validity and practicality, and are effective in improving concept understanding, learning independence, and student engagement. The findings show that STEAM-based interactive media significantly improves students’ conceptual understanding, critical thinking, and creativity, as well as fostering motivation and reducing misconceptions. Furthermore, research trends highlight the increased adoption of web-based platforms, gamification, and contextual visualization to create meaningful learning experiences.